Just Gaming: On Being Differently Literate - Kendall, Alex; McDougall, Julian (Eludamos: Journal for Computer Game Culture, 2009)
How do videogame players who are ‘by day’ engaged in formal media and literacy education understand the boundaries between playing, reading and writing in the sphere of ‘Media 2.0’ in relation to the kinds of reading practices they are obliged to be immersed in during formal learning? How might empirical witness to such cultural practices usefully inform current educational policy debates in the United Kingdom in relation to the current ‘Literacy’ and ‘Media Literacy’ agendas and their attendant discourses?   This paper presents emergent findings from a qualitative research study undertaken with a small group of 16-17 college students who are regular players of Grand Theft Auto IV. It attempts to explore the multiplicity of their ways of telling (about being, in the game) in relation to poststructuralist theories of difference and in particular Lyotard’s (1985) notion of ‘gaming’ – whereby the rules of literacy are always-already local, fluid, changing and contested. Drawing on approaches from critical discourse analysis the thoughts and reflections of the students in relation to what they think it means to read, and be a reader and to play and be a player are explored.   By giving voice to game players who are often spoken for, this paper offers findings that will be informative for colleagues with an interest in Media Literacy as social practice, as opposed to a set of competences. Thus we suggest that the use of poststructuralist critical theory (informed by Lyotard’s ‘Just Gaming’ intervention) for such discussion is neither abstract nor ‘only’ theoretical but, because the videogame as a media form resists ‘orthodox’ representational concepts, that such a theoretical context is an obligation, and of direct ‘practical’ value in the development of policy and practice around Media Literacy.